The Relationships among Quality of Online Education, Learning Immersion, Learning Satisfaction, and Academic Achievement in Cooking-Practice Subject - Yae-Ji Kim (MDPI AG, 2021)
The purpose of this study was to identify the problems of online education perceived by learners in a time when non-face-to-face online lectures are conducted due to the spread of COVID-19, and suggest measures to improve educational outcomes. Therefore, the structural influence of cooking practice on the quality of online lessons, learning immersion, learning satisfaction, and the achievement felt by learners was verified. The sample of the study was a college student majoring in cooking, and a total of 509 responses were used for analysis. The results of the study are as follows: First, it was analyzed that there was a significant influence on learning immersion in the order of content, interaction, and educational environment among the quality of online classes. Second, among the quality of online classes, class content and educational environment showed positive (+) influence on learning satisfaction. Third, learning immersion and learning satisfaction showed a positive influence on academic achievement. Fourth, in the direct effect of online class quality on academic achievement, it was analyzed that only class content had a positive (+) effect. Based on the results of this study, the provision of learning materials with detailed explanations was suggested in the online cooking practice class rather than providing a simple cooking video. In addition, it was suggested that as a way to improve academic achievement of online education, it is necessary to provide content that allows learners to immerse themselves in class, as well as class content and educational environment, and consider learning satisfaction.